Antibacterial Evaluation of Ethanolic Extracts of Four Ocimum Species against E.coli and Salmonella abaetetuba - Sahu, Rajani Kanta (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT In the present study, the antimicrobial activity whole plant ethanolic crude extracts of Ocimum sanctum, O.basilicum, O.kilimandscharicum and O.gratissimum at different concentrations (50mg/ml, 100mg/ml, 150mg/ml, 200mg/ml, 250mg/ml and 300mg/ml) was assessed and tested against two Gram-negative bacteria i.e. E.coli and Salmonell abaetetuba. Ethanolic extracts of O.basilicum showed strong antibacterial activity against E.coli followed by other three Ocimum species in more or less in equal manners. Moreover Salmonell abaetetuba was more susceptible to O.basilicum in all concentrations tested. However other three species were effective only at higher doses at 200-300mg/ml. Phytochemical analysis and nutritional contents were demonstrated the common phytonutrients like phenols, tannins, glycosides, saponins, flavonols, alkaloids, fat, carbohydrate, protein, Ca, Fe, Na etc. These phytochemicals established a good support to the use of these plants in herbal medicine and as a base for development of new drugs.